Length-weight relationship and condition factor of eight fish species from the upper Araguari River, State of Amapá, Brazil - Luiza Prestes; Marcos Sidney Brito Oliveira; Marcos Tavares-Dias; Maria Gercilia Mota Soares; Fabiana Calacina Cunha (Acta Scientiarum. Biological Sciences, 2019)
The present study estimated parameters of the length-weight relationship (LWR) and allometric condition factor for eight fish species from the upper Araguari River, in the State of Amapá, Brazil. A total of 615 fish of eight species were analyzed: Acestrorhynchus falcatus, A. falcirostris, Ageneiosus inermis, Hemiodus unimaculatus, Hoplias aimara, Myloplus asterias, M. ternetzi and Tometes trilobatus. The allometric condition factor varied from 0.742 to 1.435. The coefficient of allometry ranged from 2.723 to 3.225. The coefficient of determination (R2) of the LWR ranged from 0.742 to 0.985. This is the first estimate of the length-weight relationship for fish from the Araguari River and the first record of these parameters for Myloplus ternetzi and Tometes trilobatus.